'Power' is that which remains to be explained: Dispelling the ominous dark matter of critical planning studies. (May 2017) - Metzger, Jonathan; Soneryd, Linda; Tamm Hallström, Kristina
The purpose of this article is to contribute to the development of new theoretical and methodological resources for analysing power dynamics in planning studies. Our overarching aim is to demystify the concept of 'power' and what it purports to be describing, making those practices grouped under this label more tangible and, hence, also more readily contestable. Investigating how the effects we label as power are produced, instead of using 'power' as an all-covering explanation of societal events, demands a conceptualization of power as the outcome of social processes rather than as a causal variable behind them. An empirical study of a referendum regarding a major urban development in a Swedish suburban municipality illustrates how strong assumptions regarding the dominance of, for example, pre-existing powerful actor-constellations or purely economic relations are not always very helpful, highlighting the need for more acute attentiveness to the micro-physics of power.